Beginning T-SQL with Microsoft SQL Server 2005 and 2008 - Turley, Paul, 1962- (Wrox beginning guides., 2009)
If you've not programmed with Transact-SQL, this book is for you. It begins with an overview of SQL Server query operations and tools used with T-SQL, and covers both the 2005 and 2008 releases of SQL Server query tools and the query editor. The book then moves to show you how to design and build applications of increasing complexity. Other important tasks covered include full text indexing, optimizing query performance, and application design and security considerations. The companion website also provides all of the code examples from the book.